A simple respiratory severity score that may be used in evaluation of acute respiratory infection. (December 2016) - Rodriguez, Hector; Hartert, Tina; Gebretsadik, Tebeb; Carroll, Kecia; Larkin, Emma
Abstract Background Acute respiratory infections are ubiquitous and may have long-term implications on respiratory health. There are many scoring systems used to objectively measure severity of respiratory infections in clinical and research settings. A respiratory severity score derived exclusively from physical exam components (RSS-HR) was studied as an objective measure of disease severity and was compared to a previously described score that uses pulse oximetry as a component of its score (RSS-SO). Findings A score was derived from 497 infants. The RSS-HR median score was higher in infants that were hospitalized (8.0) versus outpatient (4.0, p < 0.001), and those with lower respiratory tract infections (LRTI) (6.5) versus upper respiratory infections (URI) (1.0, p < 0.001). When discriminating upper versus LRTIs the concordance index of regression for RSS-HR was 0.91 and RSS-SO was 0.93. Conclusions RSS-HR distinguishes disease severity based on level of care, as well as LRTI versus URI.